Juba Arabic (Arabi Juba): A 'less indigenous' language of South Sudan. (15th July 2018) - Manfredi, Stefano; Tosco, Mauro
Abstract : This article explores the official discourse behind the regimentation of the linguistic situation of South Sudan and assesses its impact on local linguistic practices against the backdrop of a sociolinguistic survey and interviews with government officials. After a presentation of the language situation of the country, the article focuses on Juba Arabic and its unrecognized status as the only lingua franca of South Sudan. The Constitution of the country nominally recognizes and enshrines the language diversity of the country, but does not come to grips with the existence of Juba Arabic, an Arabic-based pidgincreole which is the only unifying language of a vast portion of the country and the first language of the capital.